2020
DOI: 10.2147/ndt.s165931
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neuroprotective effect and mechanism of baicalin on Parkinson’s disease model induced by 6-OHDA</p>

Abstract: Objective: This research was aimed to investigate the effects of baicalin on 6-hydroxydopamine (6-OHDA)-induced rat model of Parkinson's disease (PD) and the main mechanism of baicalin based on metabolomics.Methods: The rat model of PD was induced by 6-OHDA. The protective effects of baicalin on rat model of PD were evaluated by open field test and rotarod test. The anti-PD efficacy of baicalin was evaluated by examining the morphologic changes of neurons and the level of monoamine neurotransmitters in the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…As the main active ingredient of huangqin, baicalin (BC), has been proven to have anti-bacterial and anti-inflammatory properties. It is widely used in the treatment of enteritis [10,11], influenza [12][13][14], cerebrovascular diseases [15,16]. BC has been shown to reduce cerebral infarct volume, and the pathological impairment of ischemic brain tissue has been alleviated in rats with cerebral ischemia, suggesting it has a neuroprotective effect on cerebral ischemia [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…As the main active ingredient of huangqin, baicalin (BC), has been proven to have anti-bacterial and anti-inflammatory properties. It is widely used in the treatment of enteritis [10,11], influenza [12][13][14], cerebrovascular diseases [15,16]. BC has been shown to reduce cerebral infarct volume, and the pathological impairment of ischemic brain tissue has been alleviated in rats with cerebral ischemia, suggesting it has a neuroprotective effect on cerebral ischemia [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…43 Baicalin ↓α-synuclein aggregation↑redox potential ↓neurodegeneration ↑Neurogenesis in the olfactory bulb. 44 Estrogen ↓nigral neuronal damage Controversial results as earlier estrogen was found to be an olfactory protectant and later studies suggested the opposite. 45 Omega-3 supplements ↓oxidational damage Protective against olfactory loss.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Tuan et al (2014) found that the main carotenoids in Scutellaria baicalensis were lutein (67) and β-carotene (68), and the leaves contained a lot of carotene. Lately, it was reported that three lignan glycosides (69)(70)(71) from the roots of Scutellaria baicalensis were isolated by spectral detection and qualitative chemical testing.…”
Section: Other Chemical Componentsmentioning
confidence: 99%
“…Skin autoimmune diseases, such as psoriasis vulgaris, alopecia areata and systemic lupus erythematosus (SLE) affects approximately 200 million people globally. BAI and ex vivo expanded Foxp3+ regulatory T cells were recently reported to be promising therapeutics strategy for SLE treatment since it was able to reduce Tfh cell differentiation, IL-21 production and mTOR activation while promote the differentiation of Foxp3+ regulatory T cell (Yang et al, 2019). On the other hand, BAE demonstrated reno-protective effect in a mouse model of lupus nephritis, which is regarded as a representative manifestation in SLE.…”
Section: Skin and Hairmentioning
confidence: 99%